(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper introduce the basic concepts of the theoretical description of laser- induced structural changes in solids. The approaches usedare mainly based on the calculation of the time-dependent potential energysurface and an explicit treatment of electronic degrees of freedom.Key words: Workforce diversity, disability, old age, human resource management, equal opportunity.